Fixed Asset Depreciation Information System at PT. Coca Cola Using Service Hours Method - Sitti Hariyani Siregar (Trigin Publisher, 2023)
Information System is an organizational component that collects, classifies, processes, analyzes and communicates relevant financial information for decision making to external parties (such as tax inspections, investors and creditors) and internal parties (especially management). This information system is also expected to reduce errors that occur, especially the accounting information system regarding the processing of fixed assets when producing financial information in accordance with accounting standards. Meanwhile at PT. Coca Cola is currently not using a computerized system to cover current weaknesses such as calculating the depreciation of fixed assets at PT. The Coca-Cola. For this reason, it is necessary to make an application using the Microsoft Visual Basic programming language and the Microsoft SQL Server database where it is hoped that the application will be designed to cover the current weaknesses. Where is the program made regarding the processing of fixed assets so that it can cover any weaknesses in the old system.